Hospital Volume Matters: The Volume–Outcome Relationship in Open Juxtarenal AAA Repair. Issue 1 (January 2020) - O'Donnell, Thomas F. X.; Boitano, Laura T.; Deery, Sarah E.; Lancaster, Robert T.; Siracuse, Jeffrey J.; Schermerhorn, Marc L.; Scali, Salvatore T.; Patel, Virendra I.
Abstract : Objective: We studied whether the volume–outcome relationship would persist in more complex aortic operations. Background: Despite the added complexity of the involvement of the renal arteries in open juxtarenal abdominal aortic aneurysm (AAA) repair, the volume effect in these difficult operations has yet to be defined. Methods: We identified all patients in the Vascular Quality Initiative (VQI) who underwent open AAA repair from 2003 to 2016. We calculated each hospital's average annual volume for total open AAA repairs, and total open juxtarenal AAA repairs. We compared adjusted perioperative and long-term survival across quintiles of hospital volume, and constructed models including both volume metrics to evaluate the cross-volume effects. Results: Of 8880 total open AAA repairs, there were 3470 open juxtarenal cases. Centers with low (<4), medium (4–14), and high (>14) volumes of open juxtarenal repair demonstrated adjusted perioperative mortality of 9.0%, 4.9%, and 3.9%, respectively ( P < 0.01). When both volume metrics were considered, open juxtarenal volume, but not total open AAA volume was associated with perioperative mortality (lowest quintile of juxtarenal volume: OR 2.36 [1.29–4.30], P < 0.01). Hospital volume was not associated with adjusted long-term mortality. High volume centers were more likely to use renal protective strategies such as mannitol and cold renal perfusion (both P < 0.01). Low volume centers performed a similar proportion of cases each year, but 22 centers (13%) did stop performing repairs during the study period. Conclusion: Hospitals with low annualized volumes of open juxtarenal repair have higher perioperative mortality, irrespective of their total open aortic volume. Complex open AAA repairs should be performed at experienced centers, and future efforts should focus on centralization of complex aortic care.